1992
DOI: 10.1007/bf01296569
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of precore mutant hepatitis B virus leading to fulminant hepatic failure following cytotoxic treatment

Abstract: Three hepatitis B virus carriers who were HB(e)Ag negative and having normal liver function developed fulminant hepatitis with evidence of HBV replication following intensive chemotherapy for non-Hodgkin's lymphoma. Each was continuously negative for HB(e)Ag. Analysis of the precore region of HBV isolated from each demonstrated that the HBV of each had a point mutation in the precore region that inhibited the synthesis and the release of hepatitis B(e) antigen. This observation suggests that all HB carriers re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…Among 19 published complete HBV sequences, only 3 (16%) had MO (17)(18)(19)21). Of 13 studies on pre-core HBV mutations, only 3 (23%) reported the presence of MO in a small proportion of the clones sequenced (1,3,4,(7)(8)(9)(24)(25)(26)(27)(28)(29)(30)(31). The single patient with coexistent M9 and M10 further illustrates the importance of base pairing in this stem-loop structure.…”
Section: Discussionmentioning
confidence: 99%
“…Among 19 published complete HBV sequences, only 3 (16%) had MO (17)(18)(19)21). Of 13 studies on pre-core HBV mutations, only 3 (23%) reported the presence of MO in a small proportion of the clones sequenced (1,3,4,(7)(8)(9)(24)(25)(26)(27)(28)(29)(30)(31). The single patient with coexistent M9 and M10 further illustrates the importance of base pairing in this stem-loop structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, HBsAg-positive patients could suffer from reactivation even if they remain HBeAg negative. Sequence analysis of the HBV isolated from these patients had demonstrated the presence of point mutation in the precore region that inhibited the synthesis of HBeAg [59,[72][73][74]. Therefore, it would be more reliable to demonstrate the presence of HBV reactivation by showing an increase of serum HBV DNA by quantitation.…”
Section: Pathogenesis and Diagnosis Of Hbv Reactivationmentioning
confidence: 99%
“…6 Hepatic complications related to HBV infection after hematopoietic cell transplantation are mainly related to exacerbation of HBV. [12][13][14][15][16] Before the availability of nucleoside analogue therapy for HBV infection, various agents such as interferon, 16 prostaglandin E 2 , 14 corticosteroids, 15,[17][18] and cyclosporine 16 were used to treat hepatitis due to exacerbation of HBV after immunosuppression, with largely disappointing results. With the recent introduction of effective antiviral therapy to HBV (anti-HBV) such as lamivudine 19,20 and famciclovir, [21][22][23] new treatment options are available for these patients.…”
mentioning
confidence: 99%